Prescription analysis of drug prescribed in post-operative period in a teaching hospital in Bhilai, Chhattisgarh, India - Ingole, Nishikant; Keche, Yogendra; Wankhade, Archana; Chandraker, Sunita (International Journal of Research in Medical Sciences, 2018)
Background: Surgical site infections are associated with prolonged hospital stays and increased cost of therapy. Prophylactic use of antimicrobials is to prevent the incidence of postoperative wound infection. To generate data on postoperative use of antimicrobials this study was planned. Methods: The information was collected in semi-structured questionnaire format from the patient’s case paper. Information regarding the antimicrobials prescribed by surgeon, including drug combinations, duration of therapy, frequency of drug administration, and diagnosis for the surgery was collected. Surgical wounds were classified based on National Research Council (NRC) criteria. Results: Mean duration of antibiotic use was 3.71 days for clean surgeries (70%) and ranging from 2.67 days to 6 days for clean contaminated, contaminated and dirty types of surgeries. average number of antimicrobials prescribed for surgical antimicrobial prophylaxis was 3 per patients. Ceftriaxone, cefixime, ofloxacin, levofloxacin, amikacin, amoxycillin + clavulanic acid, ampicillin, metronidazole were used for postoperative prophylaxis. Conclusions: As per guidelines, the usage of antibiotics was found to be inappropriate in some conditions. Third generation cephalosporin was the preferred or most prescribed choice of drug for postoperative prophylaxis. The average number of antimicrobials prescribed for postoperative prophylaxis was 3 per patients.